2004
DOI: 10.1002/app.13512
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of cis‐1,4‐polyisoprene catalyzed by Ru(CHCH(Ph))Cl(CO)(PCy3)2

Abstract: Hydrogenation is a useful method which has been used to improve oxidative and thermal degradation resistance of diene-based polymers. The quantitative hydrogenation of cis-1,4-polyisoprene which leads to an alternating ethylene-propylene copolymer was studied in the present investigation. To examine the influence of key factors on the reaction, such as catalyst concentration, polymer concentration, hydrogen pressure, and temperature, a detailed study of the hydrogenation of cis-1,4-polyisoprene catalyzed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The peaks at 39.8 and 26.7 ppm belonged to the CH 2 and the peak at 16.0 ppm corresponded to the CH 3 of EUG 43 . After hydrogenation, the new peaks appearing at 19.6 and 32.4 ppm were attributed to CH 3 and CH of the saturated unit, respectively, and the peaks at 37.1 and 25.4 ppm were attributed to CH 2 of the saturated unit 51 . It can be concluded that EUG was hydrogenated successfully.…”
Section: Resultsmentioning
confidence: 97%
“…The peaks at 39.8 and 26.7 ppm belonged to the CH 2 and the peak at 16.0 ppm corresponded to the CH 3 of EUG 43 . After hydrogenation, the new peaks appearing at 19.6 and 32.4 ppm were attributed to CH 3 and CH of the saturated unit, respectively, and the peaks at 37.1 and 25.4 ppm were attributed to CH 2 of the saturated unit 51 . It can be concluded that EUG was hydrogenated successfully.…”
Section: Resultsmentioning
confidence: 97%
“…Parent et al [65] described the selective hydrogenation of C=C within NBR using the homogeneous catalyst precursor, OsHCl(CO)(O 2 )(PCy 3 ) 2 in solution, which has a high hydrogenation activity for hydrogenation of NBR as well as poly-isoprene [66]. Ruthenium-based catalysts have also been used for the hydrogenation of NBR [6-12, 15, 68], polyisoprene [68,69] and PB [68,70]. Pan and Rempel [67] described an efficient catalytic system for the hydrogenation of styrene-butadiene rubber (SBR) in solution using a ruthenium complex (Ru(CH=CHPh)Cl(CO)(PCy 3 ) 2 , where Ph = phenyl, Cy = cyclohexyl).…”
Section: Catalyst Techniquesmentioning
confidence: 99%
“…The mechanism for this catalyst for the hydrogenation of cis-1,4-polyisoprene (CPIP) is slightly different [69]. As there was no clear evidence that coordination of hydrogen occurs prior to the coordination of C=C to the RuHCl(CO)(PCy 3 ) 2 , there may be two possible pathways for the hydrogenation of CPIP in the presence of Ru(CH=CH(Ph))Cl(CO)(PCy 3 ) 2 , namely an unsaturated path and a hydride path.…”
Section: Ruhclcopcy 3 2 Cnr 2 3 Rucnrhclcopcy 3 2 12mentioning
confidence: 99%
“…Venkatesh et al reported on the RAFT copolymerization of 1-octene with butyl acrylate and methyl methacrylate, while Rosales-Guzmán et al reported the copolymerization of 1-octene with glycidyl methacrylate. Another alternative to produce polyolefins involves the hydrogenation of polymer precursors such as polyisoprene (PIP) and polybutadiene (PB). This route becomes in particular important when the polymer precursor contains polar monomers in its molecular structure, and hydrogenation would lead to a polyolefin with polar properties.…”
Section: Introductionmentioning
confidence: 99%